The Trust Of Madurese Ethnic Muslims in Preventing Covid-19 Through Sya’ir Burdah: A Dimension Of Sufism in West Kalimantan - Sahri (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2023)
AbstractStudies on Madurese ethnicity in West Kalimantan began to be carried out by many academics in the aftermath of ethnic conflicts. However, there are still few who elaborate on Madurese ethnicity related to culture in West Kalimantan. In fact, the cultural richness and traditions of the Madurese ethnicity have a close relationship with Muslim cultures originating from other ethnicities. This is a social capital for strengthening solidarity and togetherness between ethnicities in West Kalimantan. This study highlights the religious traditions of the Madurese ethnic Muslim community during the COVID-19 period through the recitation of Burdah poetry, which aims to ask for safety, health, and avoiding poverty. This study also found that the Madurese ethnic Muslim community in West Kalimantan has dimensions of Sufism values in the reading of Burdah poetry such as Ikhlas, Taubat, Nur Muhammad, Mahhabba, Khauf, and Raja’. Thus, this paper elaborates on Madurese ethnic traditions and dimensions of Sufism in the Madurese ethnic Muslim community in Simpang Empat Wajok, which is currently included in the administrative area of Mempawah Regency, West Kalimantan Province. Keywords: Muslim Community, Syair Burdah, Dimension of Sufism, West Kalimantan Abstrak Kajian tentang etnis Madura di Kalimantan Barat mulai banyak dilakukan oleh para akademisi ketika pasca terjadinya konflik etnis. Tetapi, masih sedikit yang mengelaborasi etnis Madura berkaitan dengan kebudayaan di Kalimantan barat. Padahal, kekayaan budaya dan tradisi etnis Madura mempunyai hubungan erat dengan budaya Muslim yang berasal dari etnis lain. Hal ini merupakan modal sosial dalam memperkuat solidaritas dan kebersamaan antar etnis di Kalimantan Barat. Studi ini menyoroti tradisi keberagamaan masyarakat Muslim etnis Madura selama masa Covid-19 melalui pembacaan syair Burdah yang bertujuan untuk meminta keselamatan, kesehatan, dan terhindar dari kemiskinan. Kajian ini juga menemukan bahwa masyarakat Muslim etnis Madura di Kalimantan Barat terdapat dimensi nilai-nilai tasawuf dalam pembacaan syair Burdah seperti, Ikhlas, Taubat, Nur Muhammad, Mahhabba, Khauf dan Raja`. Demikian tulisan ini mengelaborasi dalam tradisi etnis Madura dan dimensi tasawuf dalam masyarakat Muslim etnis Madura di Simpang Empat Wajok yang saat ini masuk dalam wilayah administrative Kabupaten Mempawah Provinsi Kalimantan Barat. Kata Kunci: Masyarakat Muslim, Syair Burdah, Dimensi Tasawuf, Kalimantan Barat